Father’s role practices as a reflection of psychological readiness for paternity in the contemporary Chechen family - Uvaisovna, Kurbanova Lidiya; Sultanovna, Abdulaeva Elita; Zandievna, Visitaeva Irsana (Edelweiss Applied Science and Technology, 2024)
The article attempts to reveal the psychological readiness for fatherhood in a family in a local traditional society like the Chechen one. The relevance of the research topic is necessitated by a social order for studying the problems of parenting that has emerged in recent decades wherein the role of the father, according to many experts, has undergone significant transformations. The process is brought about by changes in traditional family attitudes in modern society, while under professional and economic emancipation of women, liberalization of marital relations, the focus is shifted on habitual roles, functions and requirements for parents, especially for the father. The aim of the study is to reveal the specifics of psychological readiness for fatherhood in Chechen families. We defined the constructionist approach of a modern social psychologist Kenneth J. Gergen as a theoretical framework of the study. The author employs the constructivist method within the framework of social psychology. In the context of the transformation of traditional societies, while fusing value systems of tradition, modernity and postmodernity, the use of this approach seems methodologically justified. We used a whole range of sources as the experimental part: statistical data on divorces in the country and the region, the method of inclusive observation, content analysis of research materials published on the topic, and informal in-depth interviews with fathers of families in the Chechen Republic (N = 21). Based on the analysis of the experimental part of the study, the following preliminary conclusions can be drawn: according to the surveyed fathers of families, the family as an institution should be based on basic values such as "children", "health", "communication", "respect", "spiritual closeness", "honesty", "traditions", "love". At the same time, such parameters as "career", "need for creativity" were pushed to the sidelines; socialization of the institution of parenthood, acquisition of skills of behavioral practices of the father still occurs according to respondents through the mechanisms of transfer of experience of their own parental family. Gender socialization of children in the family is recognized as meta-education by almost all surveyed fathers of families. The involvement of fathers in the upbringing of boys declared by them is not always implemented in their everyday practice. A contradiction was revealed between the preferred style of upbringing and the model of upbringing of their own parental family.